Shape memory polymers: From materials to emerging biomedical applications - Nusrat Hassan Khan (22963093) (2025)
Shape Memory Polymers (SMPs) have emerged as adaptable and promising biomaterials in biomedical engineering, enabling innovative solutions for minimally invasive procedures and personalized therapies. This review presents a comprehensive overview of SMPs, focusing on their unique shape memory effects, tuneable material properties, and emerging biomedical applications. Unlike previous reviews that primarily focused on performance enhancement through conductive fillers or crosslinking strategies, this work highlights both the tailored modification of SMP characteristics and their functional integration within biomedical contexts. Key SMP types, such as poly(lactic acid), polycaprolactone, polyurethane, poly(methyl methacrylate) and bile acid-based polymers are critically evaluated with respect to their biocompatibility, biodegradability, and responsiveness to external stimuli. Moreover, biomedical applications such as controlled drug delivery, vascular stenting, dental devices, and tissue engineering are also discussed, with particular attention to recent advances and persisting challenges. Furthermore, the review identifies essential considerations for SMP selection, including mechanical robustness, physiological compatibility, and regulatory requirements. By synthesizing current developments and outlining emerging research directions, this article provides a framework to guide both researchers and clinicians in leveraging the full potential of SMPs for next-generation biomedical devices and therapeutic platforms. Other Information Published in: European Polymer Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eurpolymj.2025.114460